Purification of A1 adenosine receptor-G-protein complexes: effects of receptor down-regulation and phosphorylation on coupling. - Gao, Z (1999)
We examined the effects of exposing A1 adenosine receptors (A1ARs) to an agonist on the stability and phosphorylation state of receptor-guanine nucleotide-binding regulatory protein (R-G-protein) complexes. Non-denatured recombinant human A1ARs extended on the N-terminus with hexahistidine (His6) and the FLAG (Asp-Tyr-Lys-Asp-Asp-Asp-Asp-Lys) epitope (H/F) were purified to near homogeneity from stably transfected Chinese-hamster ovary (CHO)-K1 cells. Purified receptors have pharmacological properties similar to receptors in membranes. G-proteins were co-purified with 15+/-2% of H/F-A1AR unless receptor-G-protein (R-G) complexes were uncoupled by pre-treating cell membranes with GTP. By silver staining, purified A1AR-G-protein complexes contain receptors, G-protein alpha and beta subunits and an unidentified 97 kDa protein. Pretreating intact cells with N6-cyclopentyladenosine (CPA) for 24 h decreased both the total number of receptors measured in membranes and the number of purified A1ARs by about 50%. In contrast, pretreating cells with CPA decreased the number of R-G complexes measured in membranes (54+/-6%) significantly less than it decreased the number of purified R-G complexes (78+/-3%) as detected by 125I-N6-(4-aminobenzyl)adenosine binding or by Western blotting Gialpha2. The effect of CPA to decrease the fraction of receptors purified as R-G complexes was not associated with any change in low-level A1AR phosphorylation (found on serine), or low-level phosphorylation of G-protein alpha or beta subunits or the 97 kDa protein. These experiments reveal a novel aspect of agonist-induced down-regulation, namely a diminished stability of receptor-G-protein complexes that is manifested as uncoupling during receptor purification.